Memahami Spektrum Autistik Secara Holistik - Ginanjar, Adriana Soekandar (UI Scholars Hub, 2007)
The purpose of this study was to understand the Autistic Spectrum (AS) by using phenomenology method. Case study was used to achieve a holistic understanding of the AS and grounded theory was used to develop a theoretical model in the explanation of AS. The data were collected from various sources: AS individuals who can communicate verbally, autobiographies, films, and experience of the researcher. Data collection method used were interviews, observations, and text analysis. Research results were delivered based on human development levels: sensory, cognitive, emotional and social interaction, and religious level. In general, sensory integration dysfunction are the main cause of AS behavioral problems. Many of autistic symptoms are usually their effort to adapt with the outside world. On a cognitive level, most AS individuals experience difficulties in verbal communication, but they usually have potential in a specific area such as drawing, music, poetry, and math. The sensory impediments also influence their emotional state and interactions. They tend to experience intense emotional state and find social interactions difficult to comprehend because of its complexity. AS individuals also find religion is difficult to understand, especially the emotional bond with God.